Advertising of Occult Services in the Modern City: The Experience of Anthropological Research in Odesa - Серебряннікова, Наталія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article is devoted to the phenomenon of occult advertising in the modern city. On the basis of advertising texts author has analyzed the specifics and peculiarities of their functioning, the influence of the urban and traditional practices regarding to informing about the occult services. In the context of the article, tradition is taken to include not just rural folk magic and divination, but also urban traditions. It emerges that as far as magic services are concerned, the range of offered services demanded by the client, largely stemming from folk tradition. By contrast discourse, approach and ritual often owe much to traditional culture, occultism and modern interest in traditional medicine.